Assessing the Effect Pender’s Model in Changing Employees’ Eating Behaviors Suffer Hypertension at Mosul University Iraq - Ahmed Salem Abbas, Nasir Muwfaq Younis (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hypertension is the most common risk factor for cardiovascular disease (CVD) , and it frequently coexists with other CVD risk factors and bad lifestyle behaviors such smoking, diabetes, cholesterol, obesity, lack of physical activity, and a poor diet. The objective of the article to identify the assessing the effect Pender’s Model in changing employees’ eating behaviors suffer hypertension at Mosul University Iraq. Method: A descriptive Cross-sectional design by using approach is conducted to determine the Assess the effect Pender’s Model in changing employees’ Eating Behaviors suffer hypertension at Mosul university Iraq. A probability simple random sample of 50 male and female employees at Mosul university Iraq. The information was gathered using a questionnaire and analyzed using SPSS version 26. Results: This results of this study that all the concepts of the pander model were (p value) significant, except for the concept of barriers. Conclusion: The study concluded that the assessment through pender’s Model showed a positive effect on many health behaviors that affect eating behavior, including perceived benefit, self_efficacy, activity related effect, and supporting family and friends to control hypertension.